Association Analysis Of Single Nucleotide Polymorphism Of Opioid Dependence Genes Among Malay Males In Malaysia - Nagaya, Devaki (2018)
Drug addiction is a chronic and relapsing disorder is associated with genetics. There are many studies have been reported the roles of single nucleotide polymorphisms (SNPs) with drug dependence and among those, twelve (12) candidate genes that were associated with drug dependence will be. investigated in this study. The candidate genes are OPRD1 (Delta Opioid Receptor), OPR.K1 (Kappa Opioid Receptor), COMT (Catechol — O-Methyltransferase gene), PDYN (Prodynorphin), DRD4 (Dopamine receptor D4), ABCB1(P glycoprotein), DUSP (Dual Specificity Phosphatase 27) and rs 10494334. The goal of this study was to determine the frequencies of these SNPs rsl042114, rs702764, rs 199774, rs 1022563, rs910080, rs737866, rs 10494334, rsl800955, rsl 128503, rsl045642, and rs2032582 and to study their association with opioid dependence in Malay males in Malaysian population.